Zerumbone-loaded nanostructured lipid carriers: preparation, characterization, and antileukemic effect - Rahman HS (Dove Medical Press, 2013)
Heshu Sulaiman Rahman,1–3 Abdullah Rasedee,1,2 Chee Wun How,2 Ahmad Bustamam Abdul,2 Nazariah Allaudin Zeenathul,1,2 Hemn Hassan Othman,1 Mohamed Ibrahim Saeed,2 Swee Keong Yeap21Department of Microbiology and Pathology, Faculty of Veterinary Medicine, University Putra Malaysia, Serdang, Selangor, Malaysia; 2Institute of Bioscience, University Putra Malaysia, Serdang, Selangor, Malaysia; 3Department of Microbiology, Faculty of Veterinary Medicine, University of Sulaimanyah, Sulaimanyah City, Kurdistan Region, Northern IraqAbstract: Zerumbone, a natural dietary lipophilic compound with low water solubility (1.296 mg/L at 25°C) was used in this investigation. The zerumbone was loaded into nanostructured lipid carriers using a hot, high-pressure homogenization technique. The physicochemical properties of the zerumbone-loaded nanostructured lipid carriers (ZER-NLC) were determined. The ZER-NLC particles had an average size of 52.68 ± 0.1 nm and a polydispersity index of 0.29 ± 0.004 µm. Transmission electron microscopy showed that the particles were spherical in shape. The zeta potential of the ZER-NLC was −25.03 ± 1.24 mV, entrapment efficiency was 99.03%, and drug loading was 7.92%. In vitro drug release of zerumbone from ZER-NLC was 46.7%, and for a pure zerumbone dispersion was 90.5% over 48 hours, following a zero equation. Using the MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay in human T-cell acute lymphoblastic leukemia (Jurkat) cells, the half maximal inhibitory concentration (IC50) of ZER-NLC was 5.64 ± 0.38 µg/mL, and for free zerumbone was 5.39 ± 0.43 µg/mL after 72 hours of treatment. This study strongly suggests that ZER-NLC have potential as a sustained-release drug carrier system for the treatment of leukemia.Keywords: zerumbone, nanostructured lipid carrier, leukemia